Efficient drug delivery by polyethylenimine capped CdSe/ZnS quantum dots and their biological activity. (August 2022) - Li, Lin-Song; Zhang, Zhi-Qiang; Zhang, Yanbin; Liu, Yong-Fang; Zhao, Mei-Xia
Graphical abstract: The low molecular weight PEI modified CdSe/ZnS QDs to form a nano-drug delivery system (CdSe/ZnS@PEI-cHCPT). CdSe/ZnS@PEI-cHCPT could induce apoptosis by mediating formation of excessive reactive oxygen species (ROS), down regulation of Bcl-2 protein and up regulation of P53, Bak and PARP-1 proteins. And CdSe/ZnS@PEI-cHCPT had good biosafety and effectively enriched at the tumor site to improve the treatment effect, suggesting the efficacy of the drug delivery system. Highlights: The nano-drug delivery system (CdSe/ZnS@PEI-cHCPT) was synthesized by low molecular weight PEI modified CdSe/ZnS QDs. CdSe/ZnS@PEI-cHCPT could induce apoptosis by mediating formation of excessive ROS, down regulation of Bcl-2 protein and up regulation of P53, Bak and PARP-1 proteins. CdSe/ZnS@PEI-cHCPT could effectively inhibit the proliferation of tumors in mice. CdSe/ZnS@PEI-cHCPT had good biosafety and effectively enriched at the tumor site to improve the treatment effect. CdSe/ZnS@PEI-cHCPT could be considered as a new type of HCPT containing nano-drug delivery system that would be employed for the treatment of cancers in near future. Abstract: Quantum dots (QDs) receive widespread attention for delivery of drugs, probing and bio-imaging exploiting their unique properties. Herein, we developed CdSe/ZnS QDs by modified low molecular weight polyethyleneimine (PEI) and conjugated them covalently with anticancer drug 10-hydroxycamptothecin (HCPT) to form a nano-drug delivery system (CdSe/ZnS@PEI-cHCPT). CdSe/ZnS@PEI-cHCPT could efficiently inhibit the proliferation of HeLa as well as other cancer cells. Moreover, CdSe/ZnS@PEI-cHCPT mediated formation of excessive reactive oxygen species (ROS), down regulation of the expression of Bcl-2 protein and up regulation of the expression of P53, Bak and PARP-1 proteins were found to be the molecular mechanisms underlying the effective anti-cancer potential of the nano-drug delivery system. Further, CdSe/ZnS@PEI-cHCPT displayed efficient therapeutic effect in inhibiting tumor growth in mice and had good biosafety and effectively enriched at the tumor site to improve the treatment effect, suggesting their great potential for future biomedical applications.